The patriarchal speech through brazilian popular music: an analysis of the missionary songs of the 20th century - Ribeiro, Arilda Ines Miranda (2018)
This article intends to conduct a preliminary discussion about the female representations contained in Brazilian songs of different musical genres that became popular in the country in the middle of the 20th century. Supported by feminist theory, the reflections intend to analyze the following songs contained in the popular local songbook: “Morocha”, by Mauro Ferreira and Roberto S. Ferreira; “Mulher Indigesta” by Noel Rosa; “Cabocla Tereza”, by João Pacífico; “Me Lambe” by Raimundos and “Mulher Vulgar”, by Racionais Mc’s explaining the patriarchal discourses related to them, in order to prove that patriarchal culture is naturalized through musical culture in Brazil. In this sense, each music chosen for analysis belongs to a distinct musical genre, a fact that corroborates the prerogative that misogyny permeates all musical styles, which express plural and distinct cultures. Each of the evaluated songs brings a different perspective on the feminine image, however, they have in common the fact of depreciating the woman, placing it in a position of inferiority in relation to the man. The androcentric vision reiterated and propelled through the popular songbook, perpetuates a culture of exclusion and violence against women, in this sense, it is proposed through these discussions, contribute to the deconstruction of a stereotyped and conventionalist view of gender roles. Submissão: 2018-03-15 Aceito: 2018-07-25